2020
DOI: 10.1007/978-3-030-53914-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Creativity of Entrepreneurs with Digital Technologies

Abstract: For decades, creativity has been used to generate ideas among entrepreneurs and their teams. Although extensive research has been conducted on creativity, the majority of studies have focused on traditional ways of stimulating creativity, such as focus groups, the collective notebook method, brainstorming, brainwriting, reverse brainstorming and problem inventory analysis. However, the digital age appears to challenge much of this existing work on the nature of creativity. It is clear that online creativity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 21 publications
0
18
0
2
Order By: Relevance
“…Large firms manage more easily in the capital markets, easier than startups and small companies entering the marketplace; limited financial investment is a barrier to businesses' survival and growth. Therefore, access to finance is very crucial in order for small firms to achieve their business goals [21]. Barriers to the development of entrepreneurship in Poland were studied by Jha [22] and it was found that economic and financial barriers are very influential hurdles in the entrepreneurial process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Large firms manage more easily in the capital markets, easier than startups and small companies entering the marketplace; limited financial investment is a barrier to businesses' survival and growth. Therefore, access to finance is very crucial in order for small firms to achieve their business goals [21]. Barriers to the development of entrepreneurship in Poland were studied by Jha [22] and it was found that economic and financial barriers are very influential hurdles in the entrepreneurial process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital technology entails various information and technologies, such as the latest digital media, utilised by entrepreneurs in different sectors for business development [6]. Technological developments have led to the employment of professionals, such as graphic designers to assist in designing new products or service for specific markets [6].…”
Section: Digital Marketing and E-commercementioning
confidence: 99%
“…Digital technology enabled people to express themselves on social media on various platforms, including Instagram and YouTube. These platforms have allowed business people, profes-Business, management and accounting sionals and amateurs to upload content that market their businesses [6]. Digital entrepreneurship is characterised with the pursuit of new venture opportunities, presented using the latest media and internet technologies available with the aim of attracting worldwide attention [7,8].…”
Section: Digital Marketing and E-commercementioning
confidence: 99%
“…In addition, Hisrich and Soltanifar (2021) highlights that digital technologies provide new avenues of entrepreneurship as it supports creativity and provides entrepreneurs with various different business modes that can promote new business activity. Similarly, Acs et al (2021) highlights the emergence of digital technologies can provide agents with incentives to engage in entrepreneurship as digital platforms has substantially reduced the economic cost of data and operating businesses.…”
Section: Introductionmentioning
confidence: 99%